KORELASI ASPEK KOGNITIF DENGAN PENGENDALIAN DBD - Jenti Sitorus; Efa Yusfi Asrifa; Dorce Sisfiani Sarimin; Farha Assagaff (Ensiklopedia Research and Community Service Review, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that remains a public health problem in many tropical and subtropical countries, including Indonesia. Indonesia is among the countries with a high burden of dengue disease. The purpose of this study was to determine the correlation between cognitive aspects and DHF control. A cross-sectional study design was used in this research. The study was conducted in the Mayang Mangurai neighborhood. The population consisted of all heads of households residing in the Mayang Mangurai neighborhood. The sample size was 100 people. Simple random sampling was used. A research questionnaire was used as the research instrument. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between knowledge (p-value: 0.037) and attitude (p-value: 0.002) and dengue fever control behaviors. It is recommended that community health centers strengthen health education, particularly for communities with low knowledge and negative attitudes, through interactive approaches that involve community leaders.Keywords: Dengue Fever, Knowledge, Attitudes